2019
DOI: 10.1098/rstb.2019.0101
|View full text |Cite
|
Sign up to set email alerts
|

The ecology and evolution of microbial CRISPR-Cas adaptive immune systems

Abstract: One contribution of 17 to a discussion meeting issue 'The ecology and evolution of prokaryotic CRISPR-Cas adaptive immune systems'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 104 publications
0
54
1
Order By: Relevance
“…The changes in CRISPR gene content may reflect the co-evolution of bacteria and the phages that attack them, in which phages need to escape the recognition of the CRISPR system while the bacteria need to catch more phage sequences through their CRISPR defense system [60]. Westra et al [61] also suggested that CRISPR loci can evolve very rapidly in natural environments. More research in the CRISPR content change with the bacteria-virus co-evolution theme may lead to more interesting discoveries in the CRISPR research realm.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in CRISPR gene content may reflect the co-evolution of bacteria and the phages that attack them, in which phages need to escape the recognition of the CRISPR system while the bacteria need to catch more phage sequences through their CRISPR defense system [60]. Westra et al [61] also suggested that CRISPR loci can evolve very rapidly in natural environments. More research in the CRISPR content change with the bacteria-virus co-evolution theme may lead to more interesting discoveries in the CRISPR research realm.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-Cas systems were first recognised for their role as phage defence mechanisms (3,(9)(10)(11), and can provide protection by preventing lysogenic conversion (12,13), which is an important mechanism of HGT (14)(15)(16). Although CRISPR-Cas systems can target parasitic genetic elements such as lytic phage, the xenogenic immunity provided by CRISPR-Cas may constrain HGT more broadly (17)(18)(19)(20). There is growing recognition that CRISPR-Cas systems target other mobile genetic elements (17,21,22), and it is suggested that CRISPR-Cas may play a very general role in preventing HGT by targeting integrative conjugative elements (ICE) and plasmids, or DNA that is acquired by transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Although CRISPR-Cas systems were initially characterized as phage defence mechanisms (9, 10), it is becoming increasingly clear that CRISPR-Cas systems also target mobile genetic elements (19)(20)(21)86).…”
mentioning
confidence: 99%
“…nov., was also identified in C. fetus. The mechanisms behind the selection of each system in different bacterial species [56], as well as the role of Cas system type III-D in C. fetus, remain unclear. https://doi.org/10.1371/journal.pone.0227500.g004…”
Section: Genomic Characterizationmentioning
confidence: 99%